Of Mice and Men play still - Peter Stackpole:::Creator::::::::::::
This Of Mice and Men play still shows Curley's wife (Clare Luce) and Lennie (Broderick Crawford), performing on the 'Barn Stage.' RESTRICTED USE. The originals are in the safe (2 copies).